Criminal policy in the domain of freezing terrorist funds and its role in addressing crime - كمال, براء منذر; رشيد, مريفان مصطفى (Journal of Legal Sciences, 2019)
It emerged as the issue of counter - terrorism recently on international levels and internal as a result of the increase in terrorist acts and committed in various countries، resulting in loss of lives and money so concerned with countries in this issue and the need to combat and eliminate the negative destructive effects that have become affect the prestige and integrity of States and stability. As a result followed criminal legislation at the international and domestic incriminatory policy may be varied somewhat in order to confront terrorist crimes by criminalizing certain acts that constitute the crime of terrorist At the international level ، several global and regional international conventions held to combat this phenomenon and at the domestic level has been many put Of the anti-terrorism laws in various countries، but the increase in the rate of terrorist crimes for various reasons has led to the inability of the aggressor States to deal with these crimes and fight them alone، so international cooperation was a welcome haven and hope . to face very serious criminal terrorism on the international community. It was to finance the regaining by terrorism ، whether as organizations terrorist or as a person significant impact on the ability of this terrorism in various countries and places of civil and non - civil and interests targeting has not been spared from the terrorist threat to any one، so it was legislative confrontation through domestic legislation of States driven and backed by a lot of poverty a Rat United nations، which contributed to an active role in the criminalization of terrorism in all its forms along with finance، the most important of which is issued in this regard put obligations on states to reduce this phenomenon so as not to allow countries to make its territory the scene of terrorist organizations and compel it to  . People arrested and prosecuted terrorists and stressed the need to join international terrorism and to prevent cutting feeders and take the necessary funding for their implementation and exchange of information and the need to cooperate to eliminate terrorism and prevent the causes and drying all the financing of terrorist groups measures treaties.